Mengembangkan Kurikulum Responsif untuk Pendidikan Inklusif: Strategi untuk Meningkatkan Akses dan Kesetaraan dalam Pendidikan Dasar - Sola, Ermi; Djasdar, Maryam; Rinayanti, Rinayanti (Lembaga Yasin AlSys, 2025)
Inclusive education requires a learning system that accommodates the diversity of learners, including children with special needs, to ensure access, participation, and equity at the primary education level. This study aims to examine the concept, characteristics, and implementation strategies of a responsive curriculum as an approach that supports inclusive primary education. The method used is a literature review, focusing on relevant scholarly works published within the past five years. The findings indicate that developing a responsive curriculum necessitates the application of differentiated instruction, modifications in assessment systems, continuous teacher training, and supportive policies and infrastructure aligned with inclusive principles. The successful implementation of a responsive curriculum depends heavily on the active involvement of all stakeholders, including teachers, parents, policymakers, and the broader community. Thus, a responsive curriculum functions not only as a technical instructional tool but also as a tangible expression of a commitment to social justice and the right to education for all learners.